The Effect of Learning Media on Language Competence in Elementary School Students: Meta-Analysis Study - Novi Asmarani Kusuma Dewi; Siti Rochmiyati; Wan Irham Ishak (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Language competency is a complex ability related to four skills at once. Many studies also state that using media in learning can improve language competence. For this reason, the research results should be evaluated to determine whether the study results can be trusted and accounted for statistically. For this reason, this research aims to compile and statistically evaluate the results of an independent study that examines learning media on language competence in elementary school students. The research method used is meta-analysis research. The study search was conducted from 2018 to 2023 in the Google Scholar database. The search results provided 108 studies that met the inclusion requirements for extraction, resulting in 111 data comparisons being examined. Calculate the magnitude of the effect of learning media on language competence in elementary school students using Microsoft Excel. This research obtained an effect size of 2.180 in the Very Large category, with a mean population correlation coefficient of 0.581. These results indicate a positive influence between the learning media teachers use on elementary school students' language competence. For this reason, it is recommended to develop or use media in language learning so that elementary school students' language competence can increase, in addition to the need for further research involving many studies related to this competence. Keywords: Language Competence, Learning Media, Meta-Analysis Study